The Synergity of the Government Budget (TAPD) Budget and the DPRD Budget Agency in The Process of The Preparation and Determination of The Budget Income and Revenue (APBD) in the Province of West Sulawesi - Andi Fitri Rahmadhany (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2019)
The purpose of this study is to describe and analyze the synergy of the RegionalGovernment Budget Team (TAPD) of West Sulawesi Province and the DPRD BudgetBoard in the process of preparing and determining the West Sulawesi Province APBDso as to achieve success in subsequent budget years, to describe and analyze the factorswhich is an obstacle in the formation of synergy in the process of drafting APBD inWest Sulawesi Province 2017 Fiscal Year and to describe and analyze the efforts madeby the Regional Government Budget Team (TAPD) of West Sulawesi Province and theDPRD Budget Board in the process of drafting APBD in West Sulawesi Province FiscalYear 2017. This type of research is qualitative. The sampling technique uses purposivesampling. Data collection techniques using observation, documentation, semitructuredinterviews, and triangulation techniques. The results of this study are the process ofpreparing and determining the West Sulawesi Province APBD in 2017 that there is stillno good synergy between TAPD and the DPRD Banggar, so this affects the quality ofthe West Sulawesi Province APBD in 2017. Factors that support or hinder theformation of synergy in the process of drafting and APBD determination in WestSulawesi Province 2017 Fiscal Year is an element of interest from both the regionalgovernment and the Regional Representative Council (DPRD), the program prioritiesagreed upon by the Regional Government Budget Team are not in line with theprogram priorities desired by the DPRD Banggar.